2017
DOI: 10.1002/ange.201701761
|View full text |Cite
|
Sign up to set email alerts
|

Common Fibril Structures Imply Systemically Conserved Protein Misfolding Pathways In Vivo

Abstract: Systemic amyloidosis is caused by the misfolding of ac irculating amyloid precursor protein and the deposition of amyloid fibrils in multiple organs.C hemical and biophysical analysis of amyloid fibrils from human AL and murine AA amyloidosis reveal the same fibril morphologies in different tissues or organs of one patient or diseased animal. The observed structural similarities concerned the fibril morphology,t he fibril protein primary and secondary structures,t he presence of post-translational modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…It is also seen when analysing amyloid fibrils extracted from patients or animal diseased with amyloidosis. A comparative analysis of fibrils extracted from different forms of amyloidosis revealed polymorphic fibril morphologies based on electron microscopy, and this result was independent of the type of amyloidosis analysed, the amyloid‐forming protein, and the organ involved in the amyloid deposition . Changing the conditions of fibril formation in vitro can alter the distribution of fibril polymorphs present in a sample .…”
Section: Amyloid Fibril Polymorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also seen when analysing amyloid fibrils extracted from patients or animal diseased with amyloidosis. A comparative analysis of fibrils extracted from different forms of amyloidosis revealed polymorphic fibril morphologies based on electron microscopy, and this result was independent of the type of amyloidosis analysed, the amyloid‐forming protein, and the organ involved in the amyloid deposition . Changing the conditions of fibril formation in vitro can alter the distribution of fibril polymorphs present in a sample .…”
Section: Amyloid Fibril Polymorphismmentioning
confidence: 99%
“…Similar to observations made with fibrils extracted from systemic ATTR amyloidosis, it was found that different patients were associated with different ensembles of fibril morphologies. Interestingly, however, within the same patient, consistent fibril morphologies were seen in the different tissues (heart muscle, heart fat and abdominal fat) . Detailed fibril structures by cryo‐EM are currently available for a 12‐residue peptide fragment of an amyloidogenic light chain .…”
Section: Light Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of protein aggregation, fibrillar aggregates get deposited in the specific body tissues. 3 Amyloid fibers formed from different proteins share some common features as these are rich in β structures where β-sheets are perpendicularly arranged to the fibrillar axis. 4 The organization of fibrils, kinetics, and their overall stability is highly governed by the amino acid sequence of proteins and the surrounding environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid fibril is a type of insoluble protein that aggregate with a specific secondary structure. [3][4][5][8][9][10]. Lysozyme is not associated with any known amyloid diseases; however, it shares similar morphological features with amyloids from disease associated proteins.…”
mentioning
confidence: 99%